Membangun Inspirasi: Magang Kepala Sekolah Muhammadiyah Cirebon di Limau Bendi Kebayoran Baru - Syahrul Zamal; Dwi Priyo Utomo; Baiduri Baiduri (Universitas Pahlawan Tuanku Tambusai, 2026)
This inspirational internship activity was conducted to address the need for enhancing leadership and school management capacity within the Muhammadiyah educational network of Cirebon Regency. Held at Limau Bendi School, Kebayoran Baru, from September 15–17, 2025, the program involved school principals and board members of the Education Council. The goal is to gain direct insights into best practices in visionary leadership, learning innovation, and school culture. This community service program utilizes activity mentoring and inspiration workshops. The mentoring results identified four success pillars of Limau Bendi.The mentoring results identified four pillars of Limau Bendi's success: visionary school leadership, the application of active technology-based learning methods, high community engagement, and a strong quality-oriented school culture. The study concludes that adapting these effective practices in Cirebon schools is highly feasible, with key recommendations focusing on comprehensive training for principals, improvement of technological facilities, and strengthening a collaborative culture. Implementing these recommendations is expected to significantly drive educational quality improvement.